Macroeconomic Influences and Policy Impacts on Indonesia's Foreign Debt Accumulation - Guslaw, Helva; Septriani, Septriani (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
The issue of foreign debt as a source of development financing (budget deficit) has become a classic debate, both at the theoretical and practical levels. However, foreign debt will become a problem if the debt is not managed properly. This study aims to determine the effect of exports, foreign exchange reserves, and exchange rates on foreign debt in Indonesia. The novelty of this research is that the population in this study is the entire time series data of foreign debt, exports, foreign exchange reserves, and the exchange rate of the rupiah against the US dollar. The future impact of this study is to help improve public understanding of the urgency of the determinants and influence of foreign debt in Indonesia for the government. This research is a type of quantitative descriptive research. The type of data used is data sourced from secondary data in the form of cross-section covering the country of Indonesia and time series with a period of 30 years so that there are 31 samples that are quantitative. The research was conducted by means of library research. Data collection techniques are carried out by studying books that are relevant to the object of research or other sources that support library study research conducted by researchers in conducting library studies. Based on the regression result, it can be concluded that there is a simultaneous significant effect of the independent variables in the form of Exports, Foreign Exchange Reserves, and the Rupiah Exchange Rate against the USD on the Foreign Debt with an R-Squared value of 92.11 percent. Then, based on the partial Test, export has a negative and significant effect on the foreign debt. Meanwhile, each foreign exchange reserve and Rupiah exchange rate have a positive and significant effect on the Foreign Debt. The policy implications of these findings can include government efforts in the hope of finding other alternatives to increase Indonesian state development funds other than relying on foreign debt. For example, it can be done by increasing export activities abroad and reducing import activities. Furthermore, maintaining the stability of the exchange rate so that it does not weaken further because it can result in a decrease in the value of the US dollar, making foreign debt in Indonesia increasingly accumulate.